Extracting and Representing Entities from Open Sources of Information in the Agatha Project - Carnaz, Gonçalo (2018)
The Agatha project aims to develop an intelligent system that resorts to open sources (video, audio and text) of information for surveillance and crime control. Named-entity recognition combined with ontologies is the approach followed for the textual sources. This work describes the theoretical basis together with the system implementations for the text analysis component of the Agatha framework.